The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1002/joc.3370050410
|View full text |Cite
|
Sign up to set email alerts
|

Canyon geometry, street temperatures and urban heat island in malmö, sweden

Abstract: The paper demonstrates the relevance of sky view factor analysis in urban canyons to thermal features of the surface and air in the urban canopy layer at night. The result of the study, made in the city of Malmo (population about 230,000) in southern Sweden, indicates, among other things, that the street geometry and its regional distribution within the city area plays a fundamental role in generating the street surface temperature pattern of the city, its 'surface heat island'. The paper also demonstrates a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
2
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 7 publications
(9 reference statements)
5
76
2
4
Order By: Relevance
“…Several authors have shown a relationship between surface temperature and sky view factor, which has statistical significance for several areas (Bärring et al 1985;Eliasson 1996;Upmanis 1999;Postgård 2000;Chapman et al 2001b). This is expected since the energy balance of the surface controls the surface temperature.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several authors have shown a relationship between surface temperature and sky view factor, which has statistical significance for several areas (Bärring et al 1985;Eliasson 1996;Upmanis 1999;Postgård 2000;Chapman et al 2001b). This is expected since the energy balance of the surface controls the surface temperature.…”
Section: Introductionmentioning
confidence: 95%
“…Eliasson (1996) found no statistical significance between street canyon geometry and air temperature in the central parts of Göteborg. In a study of another Swedish city, Malmö, Bärring et al (1985) concluded that air temperature was not as strongly correlated to street canyon geometry as the surface temperature. In Japan, however, a fairly strong relationship was found between air temperature and SVF in cities such as Fuchu and Higashimurayama (Yamashita et al 1986).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, into 2 separate parts. In the first part, the basic data is field observations (Barring et al 1985) and simulationclassified with respect to cloudiness and, in the second, based studies (Todhunter 1990) have shown that the data is analysed by multiple regression. heterogeneous urban microclimate is attributable to the variable urban geometry within a given land-use category.…”
Section: Introductionmentioning
confidence: 99%
“…Bärring et al [71] reported that increasing SVF led to a decrease in surface temperature in Malmö, Sweden. However, consensus on whether there is a clear correlation between air temperature and SVF has not been achieved.…”
Section: Space Enclosure Descriptorsmentioning
confidence: 99%